The role of adsorbents in the management of diarrhea syndrome in children - O.Yu. Belousova; L.G. Voloshyna; O.M. Вabadzhanian; O.B. Hanzii; K.V. Voloshyn (Zaslavsky O.Yu., 2018)
This article deals with the pathological conditions with diarrhea syndrome in children. Pathogenetic mechanisms of diarrhea development, peculiarities of clinical and laboratory manifestations in various diseases are considered. The main methods to control diarrhea are presented, mechanisms of sorption therapy action are considered. The classification of enterosorbents used in clinical pediatric practice is given. The characteristics of Apsorbin sachet which is registered in Ukraine as dietary supplement with enterosorption action is given. The results are presented on using Apsorbin sachet in comprehensive therapy of children with irritable bowel syndrome (type with diarrhea) and convalescent children after gastrointestinal infections.